Empowering Islamic Education Teachers as Special Assistants to Support Inclusive Elementary Schools - Dina Hermina; Muhamad Sabirin; Apriana Afifah; Dilah bin Tuah (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
The importance of inclusive Islamic education is increasingly recognized in ensuring educational quality for students with special needs. This study sought to answer how training for Islamic Education teachers as special assistants is planned, implemented, evaluated, and followed up in inclusive elementary schools in Tapin Regency, Indonesia. Methods: This qualitative exploratory study was conducted in four elementary schools (Mandurian Public Elementary School, Pematang Karangan Hulu Public Elementary School, Rantau Kanan 2 Public Elementary School, Pebaungan Hulu Public Elementary School) involving eight Islamic Education teachers as special assistants. Data were collected through in-depth interviews, focus group discussions, and observations, and analyzed using data reduction, presentation, and conclusion. Results: The training played a significant role in improving teachers' competencies and fostering collaborative practices, involving systematic planning through meetings with principals and work teams, workshops, training sessions, ongoing supervision, comprehensive performance evaluation. Follow-up activities included reflection, continuous training, and collaboration between assistant and regular teachers to optimize inclusive education, though hampered by resource constraints. Conclusion: Systematic and comprehensive training of Islamic Education teachers as special assistants plays a significant role in supporting the success of inclusive education for students with special needs and provides valuable insights for developing effective inclusive Islamic education programs.